Certificate making machine - WU WENHAN; LI PINGBIAO; ZHOU ZHENGSHI (2022)
The utility model relates to a certificate making machine. The certificate making machine comprises a machine base, and a color printer, a character printer, a cutting device, a film laminating and laminating device and a conveying device which are arranged on the machine base, the color printer is used for printing pictures or photos on the certificate cores, the character printer is used for printing characters on the certificate cores, the cutting device is used for cutting the certificate cores into preset styles, and the laminating and laminating device is used for laminating the certificate cores and heating and laminating the laminated certificate cores. The certificate core printed by the character printer passes through the cutting device and the film and plastic laminating device in sequence; the conveying device comprises a machine frame arranged on the machine base, an upper conveying assembly and a lower conveying assembly, the upper conveying assembly and the lower conveying assembly are arrange